Multi-scale evaluation of ecological restoration effects in the riparian zone using Landsat series images from 1980 to 2019. (December 2021) - Yang, Gao; Li, Ying; Huang, Tieqing; Fu, Bolin; Tang, Jing; Zhang, Xing; Wu, Jisheng
Highlights: Long-term monitoring of riparian condition based on RS method were achieved. We proposed a new multi-scale evaluation strategy for riparian restoration. Ecological partitioning was useful to identify fragile areas and influence factors. The riparian zone with a higher PSI index did not indicate a better restoration effect. Indicators suitable for plain rivers need further development for wider application. Abstract: Quantitative evaluation of ecological restoration effects (EREs) is essential to provide operational feedback and implement adaptive management for future riparian restoration. This manuscript aims to develop a multi-scale evaluation method of EREs based on remote sensing observations, which uses the composite index of physical structural integrity (PSI) to indicate riparian condition. The riparian EREs were quantitatively assessed by comparing the post-restoration PSI values with the ecological reference status derived from pre-restoration surveys. In addition, ecological partitioning was adopted to identify the vulnerable riparian areas and explore the influence indicators of ecological restoration. In this paper, we used the case study of the Liaohe River, the first protected area aimed to recover the riparian ecosystem in China, to evaluate the riparian EREs at three spatial scales using Landsat time series images from 1980 to 2019. Results indicated that: (1) the pre-restoration riparian ecosystem exhibited an clear degradation trend and ecological conservation was urgent; (2) riparian restoration is a continuous and heterogeneous ecological process, the project had not yet met its objectives in 2016 with a low ERE value of 49.1 (Poor), while achieved a significant success in 2019 with the ERE value of 68.8 (Very good); (3) the limited restoration partitions with a ERE value below 60 accounted for 42.8% of riparian zones, which were the fragile riparian ecosystems and mainly distributed in reach D and F; and (4) the dominant factors for riparian restoration were canopy coverage, human disturbance and natural vegetation percent. This study is expected to provide a practical and feasible approach for evaluating the riparian EREs and supporting the future river management, in particular for rivers lack of long-term monitoring data.